Beberapa Model Pembelajaran Pendidikan Teknologi dan Industri Kontemporer - Achmad Tutjik Moechid (Universitas Negeri Malang, 2016)
Education in Indonesia should be directed to the actual needs of society, for today and tomorrow. Curriculum should contain an appropriate portion of technology which meets the future needs of society. The special nature of industrial arts allows it to have far reaching relationships with other subject areas; serve as a means of developing knowledge, enable students to examine technological alternatives to societal problems; provide an opportunity to explore change as an element of life; and help students explore how they can make a contribution in a future society. By looking into the future, people may be more adequately attuned to the life experiences of the world in which they are about to live